Artemisia verlotiorum Lamotte (Asteraceae), especie alóctona invasora en Andalucía (sur de España). - Quesada Rincón, Juan; Valle Tendero, Francisco; Salazar Mendías, Carlos (Acta Botanica Malacitana, 2008)
Artemisia verlotiorum Lamotte (Asteraceae), an allocthonous invasive species in Andalusia (southern Spain) Palabras clave. Corología, Jaén, provincia Luso-Extremadurense, plantas invasoras, vegetación riparia. Key words. Chorology, Jaen, Luso-Extremadurensian province, invasive plants, riparian vegetation.